Modified Vacuum Assisted Closed Delivery Administration of High Dose Radio Iodine Through Gravity Augmentation - “Faster and Safer Technique” - Ranadheer Gupta Manthri; Hemalatha Pottumuttu; Vatturi Venkata Satya Prabhakar Rao (Indian Journal of Nuclear Medicine, 2026)
High dose radio iodine administration has passed through the conventional open suction method, with its drawbacks and dangers of spillage and excessive exposure to radiation personnel. This was followed by the closed system vacuum-assisted technique. The latest innovation is the gravity augmented administration, which further reduces exposure to radiation personnel by faster consumption by the patient. This technique is easy using simple and easily available materials.